2020
DOI: 10.3390/ijerph17082671
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Questionnaire Developed to Evaluate a Pediatric eHealth Website for Parents

Abstract: There is a need for health professionals to provide parents with not only evidence-based child health websites but also instruments to evaluate them. The main aim of this research was to develop a questionnaire for measuring users’ evaluation of the usability, utility, confidence, the well-child section, and the accessibility of a Spanish pediatric eHealth website for parents. We further sought to evaluate the content validity and psychometric reliability of the instrument. A content validation study by expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…The aim of this study was to show and discuss the validation process and the adaptation to the Italian context of a questionnaire on consumer knowledge and attitudes toward sustainability starting from a questionnaire already used in Europe [ 18 ]. Using a procedure largely described in the literature [ 25 , 26 , 27 , 28 ], the questionnaire was initially developed by experts and then revised on the basis of the results of a pilot test on consumers. The analysis of the data collected in the pilot phase on a group of 150 respondents, highlighted a series of inconsistencies that were corrected in the final version of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to show and discuss the validation process and the adaptation to the Italian context of a questionnaire on consumer knowledge and attitudes toward sustainability starting from a questionnaire already used in Europe [ 18 ]. Using a procedure largely described in the literature [ 25 , 26 , 27 , 28 ], the questionnaire was initially developed by experts and then revised on the basis of the results of a pilot test on consumers. The analysis of the data collected in the pilot phase on a group of 150 respondents, highlighted a series of inconsistencies that were corrected in the final version of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire validation protocol was designed following a procedure largely reported in the literature [ 25 , 26 , 27 , 28 ], applied in different settings, and assessing different topics and constructs. The procedure could be summarized as follow: the initial analysis for the identification of the domains of interest was normally carried out by the team that developed the questionnaire [ 29 ], then the validity of the items was assessed in consecutive stages by requesting individual experts to evaluate the content relevance and simplicity of individual items and the entire set of items (questionnaire) as a tool [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, the adequacy of the sample size was determined by the Kaiser‐Meyer‐Olkin statistic. A Kaiser‐Meyer‐Olkin value of ≥ .80 indicates high adequacy of sample size (Nievas Soriano et al., 2020). In this study, Kaiser‐Meyer‐Olkin in the exploratory factor analysis was .85.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical tests were used to estimate the required sample value to calculate effect sample values for the questionnaire analysis. The estimate revealed that more than 110 responses were needed for each type, and over 220 in all to ensure the study's accuracy [67][68][69]. Thus, according to the estimation, the sample amounts were sufficient to perform an accurate and useful study.…”
Section: Questionnaire Surveymentioning
confidence: 99%